2013
DOI: 10.1029/2012jd018653
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation of gravity wave momentum flux and its forcing on the diurnal tide

Abstract: [1] The diurnal variation of gravity wave (GW) momentum flux is derived from the 5 years of meteor radar wind measurements at Maui, Hawaii. The amplitude and phase relationships between the GW forcing and the diurnal tide are analyzed by calculating their equivalent Rayleigh frictions. The results show that the GW momentum flux is clearly modulated by the diurnal tide. The forcing from the momentum flux convergence has strong effects on both the amplitude and phase of the diurnal tide. They can reach 80 msfor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 56 publications
(104 reference statements)
4
54
0
Order By: Relevance
“…The anti-correlation is seen during all the few multi-day runs of the MU radar that made meteor observations. This finding is also consistent with the behavior reported by Liu et al (2013), using a meteor radar on Maui, Hawaii.…”
Section: Hocking Technique Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The anti-correlation is seen during all the few multi-day runs of the MU radar that made meteor observations. This finding is also consistent with the behavior reported by Liu et al (2013), using a meteor radar on Maui, Hawaii.…”
Section: Hocking Technique Resultssupporting
confidence: 93%
“…Such radars can be comparatively modest in size and cost, and can make round the clock observations of the winds. The technique has been widely adopted (e.g., Antonita et al, 2008;Fritts et al, 2010Fritts et al, , 2012Placke et al, 2011a,b;Andrioli et al, 2013;Liu et al, 2013;de Wit et al, 2015). However, there have been some lingering concerns as to whether statistically meaningful estimates of momentum fluxes can be made over timescales of interest to modellers (Vincent et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Fritts and Vincent [] calculated the time difference to be approximately 2 h. Liu et al . [] reported that the meridional momentum flux and the diurnal tide are approximately 90° out of phase (~6 h). Likewise, the phase of momentum flux also shows seasonal variation with tides.…”
Section: Resultsmentioning
confidence: 99%
“…Antonita et al, 2008;Clemesha and Batista, 2008;Mitchell, 2009, 2010;Clemesha et al, 2009;Fritts et al, 2010aFritts et al, , b, 2012aVincent et al, 2010;Placke et al, 2011aPlacke et al, , b, 2014Placke et al, , 2015Andrioli et al, 2013aAndrioli et al, , b, 2015Liu et al, 2013;de Wit et al, 2014bde Wit et al, , a, 2016Matsumoto et al, 2016;Riggin et al, 2016). This has largely arisen from a need to obtain improved spatial coverage in the parameterization of GWs and their associated momentum transport in climate models of the whole atmosphere (e.g.…”
Section: Introductionmentioning
confidence: 99%